The Function and Diversity of Plastid Protein Import Pathways : A Multilane GTPase Highway into Plastids - Kessler, Félix; Schnell, Danny J. (My University, 2006)
The photosynthetic chloroplast is the hallmark organelle of green plants. During the endosymbiotic evolution of chloroplasts, the vast majority of genes from the original cyanobacterial endosymbiont were transferred to the host cell nucleus. Chloroplast biogenesis therefore requires the import of nucleus-encoded proteins from their site of synthesis in the cytosol. The majority of proteins are imported by the activity of Toc and Tic complexes located within the chloroplast envelope. In addition to chloroplasts, plants have evolved additional, non-photosynthetic plastid types that are essential components of all cells. Recent studies indicate that the biogenesis of various plastid types relies on distinct but homologous Toc–Tic import pathways that have specialized in the import of specific classes of substrates. These different import pathways appear to be necessary to balance the essential physiological role of plastids in cellular metabolism with the demands of cellular differentiation and plant development.
Keywords: chloroplast; GTPase; plastid; proteinimport; translocon